Effects of Transcranial Direct Current Stimulation Treatment for Anorexia Nervosa - Baumann, Silvie; Mareš, Tadeáš; Albrecht, Jakub; Anders, Martin; Vochosková, Kristýna; Hill, Martin; Bulant, Josef; Yamamotová, Anna; Štastný, Ota; Novák, Tomáš; Holanová, Petra; Lambertová, Alena; et al. (Frontiers in Psychiatry, 2021)
Background: Anorexia nervosa (AN) is a life-threatening illness with poor treatment outcomes. Although transcranial direct current stimulation (tDCS) is a promising non-invasive brain stimulation method, its effect in patients with AN remains unclear. Objective: This study investigated changes in maladaptive eating behavior, BMI and depression after 10 sessions of anodal tDCS over the left dorsolateral prefrontal cortex (DLPFC). Methods: In this double-blind, randomized controlled trial, forty-three inpatients with AN were divided to receive either active (n=22) or sham (n=21) tDCS over the left DLPFC (anode F3/cathode Fp2, 2mA for 30 minutes). All patients filled the Eating Disorder Examination Questionnaire (EDE-Q), Zung Depression Scale (ZUNG) and their BMI was measured. These values were obtained repeatedly in 4 stages: (1) before tDCS treatment, (2) after tDCS treatment, (3) in the follow-up after 2 weeks, and (4) in the follow-up after 4 weeks. Results: Primary outcomes (EDE-Q) based on the ANOVA results do not show any between-group differences either after the active part of the study or in the follow-up. Secondary analysis reveals a reduction in some items of EDE-Q. Compared to sham tDCS, active tDCS significantly improved self-evaluation based on body shape (p<0.05) and significantly decreased the need of excessive control over calorie intake (p<0.05) in the 4-week follow-up. However, the results do not survive multiple comparison correction. In both sham and active groups, the BMI values improved, albeit not significantly. Conclusion: We did not observe a significant effect of tDCS over the left DLPFC on complex psychopathology and weight recovery in patients with AN. TDCS reduced the need to follow specific dietary rules and improved body image evaluation in patients with AN. Tests with a larger sample and different position of electrodes are needed. Clinical Trial Registration: www.ClinicalTrials.gov, NCT03273205